Effect of the Solution Temperature on the Precipitates and Grain Evolution of IN718 Fabricated by Laser Additive Manufacturing - Yu Cao (Materials, 2020)
The effects of the solution heat treatment temperature on the precipitates, grain boundary evolution and response of the microhardness of Inconel 718 (IN718) superalloy fabricated by selective laser melting (SLM) were investigated. It was found that: (1) The long-chained Laves phases formed in the as-deposited condition dissolved into the matrix when the solution temperature rises above 980 °C. (2) The width-to-length ratio was maintained at approximately 1.6 when the solution was heated from 980 °C to 1080 °C, and dropped down to 1.03 when heated to 1130 °C. (3) Low-angle grain boundaries kept the same number fraction of 65% from 980 to 1080 °C as the as-deposited condition, and decreased dramatically from 1090 to 1130 °C to 4%. (4) Annealing twin boundaries occurred at 1090 °C with a number fraction of 3%, and quickly increased to 65% when heated to 1130 °C. It is concluded that the static recrystallization of IN718 fabricated by selective laser melting (SLM) occurred at 1090 °C and fast proceeded to full recrystallization at 1130 °C. The forming of annealing twins accompanies the recrystallization process and is an effective way to refine the recrystallized grain size.